Fabrication of ultra-sensitive and disposable electrochemical biosensor: Detection of kidney injury molecule-1 protein in urine for diagnosis of kidney injury - Elif Ceren Ankara; Sude Aras; Burçak Demirbakan; Mustafa Kemal Sezgintürk (Journal of Pharmaceutical and Biomedical Analysis Open)
This research study indicates the development of the indium tin oxide-polyethylene terephthalate (ITO-PET) coated electrode-based electrochemical biosensor system to sensitively and specifically detect kidney injury molecule-1 (KIM-1), an acute kidney injury (AKI) biomarker. The ITO-PET electrode surface was modified with 3-(Trimethoxysilyl)-1-propanethiol (3-TMESP) silane agent. Electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), and single frequency impedance (SFI) techniques were utilized to examine the interactions between anti-KIM-1 antibody and KIM-1 antigen. The ITO-PET electrode surface was observed by scanning electron microscopy (SEM) and atomic force microscopy (AFM) to analyze the morphological characterization at each electrode development stage. Optimization studies have been conducted to determine the optimal concentrations for detecting the 3-TMESP silane agent, the NHS crosslinker, the anti-KIM-1 antibody, and the optimum incubation period for the anti-KIM-1 antibody and the KIM-1 antigen. Analytical characteristic properties of the developed biosensor, including linear determination range, and the studies of reproducibility, regeneration, repeatability, storage life, and selectivity were investigated. The KIM-1 biosensor system, based on 3-TMESP, has a broad linear range and is capable of providing sensitive measurements between 0.1 fg/mL and 1000 fg/mL. The values of low limits of detection (0.26 fg/mL) and of quantification (0.87 fg/mL) were calculated, highlighting its high sensitivity and precision in detecting KIM-1. In addition, five different commercially purchased human urine samples were tested to validate the practicability of the developed biosensor.